Managing fire for woodland caribou in Jasper and Banff National Parks - Landon Shepherd; Fiona Schmiegelow; Ellen Macdonald (Rangifer, 2007)
Woodland caribou (Rangifer tarandus caribou) populations in Jasper (JNP) and Banff National Parks (BNP) have declined since the 1970s, coincident with reduced fire activity in both parks, relative to historic levels. Some researchers have suggested that long periods without fire may cause habitat deterioration for woodland caribou, primarily by reducing available lichen forage. We examined winter habitat selection by woodland caribou at coarse and fine scales based on GPS-derived telemetry data and used models that included stand origin (decade), topography, and several stand structure variables that are related to time since fire, to explore relationships among caribou, lichen, and fire history. Based on the relationships illustrated by the models, we assessed how fire management could be applied to caribou conservation in JNP and BNP. At a coarse scale, caribou selected old forest (> 75 years) in landscapes that have likely experienced less frequent wildfire. While the abundance of Cladonia spp. influenced caribou use at fine scales, a preference for areas with older trees within stands was also significant. We conclude that short-term habitat protection for woodland caribou in JNP and BNP likely requires fire exclusion from caribou range.